Analysis of the Efficacy and Safety of Weekly Calcifediol 100 µg in Vitamin D Deficient Patients - Pérez Castrillón, Jose Luis; Jódar-Gimeno, Esteban; Molina, Koldobika; García-Bea, Aintzane; Ostalé, Cristina Martínez; Gilaberte, Inmaculada (Journal of clinical medicine, 2025)
Background/Objectives: Adequate vitamin D levels are critical for overall health, yet vitamin D deficiency remains prevalent. This study aims to evaluate the efficacy and safety of a standardized weekly supplementation regimen of 100 μg calcifediol for patients with varying degrees of vitamin D deficiency. Methods: A post hoc pool analysis was conducted from a randomized, double-blind, placebo-controlled, multicenter, two-cohort trial. Cohort 1 included vitamin D mild deficiency patients (25(OH)D levels > 10 < 20 ng/mL) and Cohort 2 severe deficiency patients (25(OH)D levels ≤ 10 ng/mL). As both had placebo and weekly calcifediol 100 μg arms (ratio 1:2), a pooled analysis of safety and efficacy was conducted. The primary outcome was the percentage of subjects achieving 25(OH)D levels ≥ 20 ng/mL and/or ≥30 ng/mL at various time points. Results: A total of 401 participants across both cohorts were included in the analysis, 130 who received a placebo and 271 calcifediol 100 µg weekly. By week 52, 94.5% of individuals in the calcifediol group achieved 25(OH)D levels ≥ 20 ng/mL, compared to 25.3% in the placebo group (p < 0.0001). At this same week, 80.5% of subjects in the calcifediol group, but none in the placebo group (p < 0.0001), had 25(OH)D levels ≥ 30 ng/mL. The mean 25(OH)D level plateaued around 40.7 ng/mL from weeks 16 to 52. The frequency of treatment-emergent adverse events was similar in both groups, placebo and calcifediol. Conclusions: Weekly supplementation of 100 μg calcifediol effectively restores vitamin D levels in individuals with both mild and severe deficiencies, demonstrating a favourable safety profile.